The leadership habit transforming behaviors to drive results - Berberick, Tammy R.; Lindsay, Peter; Fritchen, Katie (Wiley, 2017)
"The 10 essential skills to transform the way you lead The Leadership Habit provides the framework for patterns of behavior that will transform the way you lead. By articulating a clear, well-defined standard of what it means to be a leader, this book condenses volumes of advice and opinion into 10 key areas and teaches leaders how they can create daily habits surrounding these centers of excellence. Leaders who can commit to creating change will develop more productive teams and will build long-term growth for their organization. This book is your invaluable guide to being one of the greats, with proven advice and a concrete framework for leading well. Through expert discussion and deep dissection of these critical areas, you & rsquo;ll discover how to drive for results, build the best team, execute on vision, foster innovation, and more. Learn how to: Transform your habits across 30 specific skill areas Model personal growth, focus, and positivity Accelerate productivity and maintain your organization & rsquo;s competitive advantage As a leader, your team's performance and your organization's outlook are direct reflections of you. Discover how to become a catalyst for driving performance and results by transforming your actions every day."--
Includes index. - Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Leadership; BUSINESS & ECONOMICS; Leadership